PENGARUH EDUKASI GIZI TERHADAP POLA KONSUMSI ZAT BESI DAN KADAR HEMOGLOBIN PADA REMAJA PUTRI ANEMIA DI SMPN 29 SAMARINDA - Nurmawaddah, Salsabilya; Satriani, Satriani; Novaria, Astri Ayu (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Anemia can be prevented by providing education that will affect attitudes and food consumption behavior. One of the media that can be used is animated video which has the effect of increasing retention, attracting attention and imagination concepts, objects and their relationships may be visualized. This study aims to determine the effect of nutrition education on iron consumption patterns and hemoglobin levels in anemic adolescent girls at SMPN 29 Samarinda. The research design used was pre experimental with a one group pretest posttest design with a sample of 30 female students. The variables studied were nutrition education, iron consumption patterns and hemoglobin levels. The instruments used were hemoglobin meter and SQ-FFQ. The statistical test used is paired T-test if the data is normally distributed and wilcoxon test if the data is not normally distributed or ordinal scale. The results of the wilcoxon test showed that there is an effect of nutrition education on frequency of consuming iron sources (p=0.005) and hemoglobin levels (p=0.000). There is no effect of nutrition education on the source of iron consumed (p=1.000). The paired T-test results showed that there is an effect of nutrition education on the intake of iron sources (p=0.000).